The ACCC's Caltex-Mobil decision: A network view - Bloch, Harry; Wills-Johnson, Nick (Centre for Research in Applied Economics, Curtin Business School, 2010)
On December 2nd 2009, the Australian Competition and Consumer Commission (ACCC) announced its intention to oppose the acquisition of Mobil's retail assets by Caltex, based in part on an assessment of adverse competition effects in some local markets. Their assessment was based upon the proportion of sites within each local market that would become controlled by Caltex post-merger. This paper suggests an alternative method foranalysing competitive effects, which formalises local market structure into a network and assesses the position of each outlet in that network.